Inter-correlation and path co-eﬃcient analysis for agro-morphological and yield traits in bottle gourd (Lagenaria siceraria) - Sneha Rathore; Arjun Lal Ola; Anita Choudhary; Shivam, Kalpna; Saroj Bishnoi (Current Horticulture, 2025)
The study was carried on Inter-correlation and path co-eﬃcient analysis of bottle gourd (Lagenaria siceraria) at Vegetable Research Farm, RLBCAU, Jhansi, Uttar Pradesh during kharif 2022. A total of 30 genotypes were sown in a randomized block design with three replications. Observations were recorded on 15 characters. Higher magnitude of GCV and PCV was recorded for fruit length (cm), fruit width (cm) and yield/plant (Kg/plant). The insigniﬁcant diﬀerence between GCV and PCV was recorded for most of the traits indicated that traits were less impacted by the environment. The inter-character association at phenotypic and genotypic correlation coeﬃcients suggested that yield/plant recorded highly positive signiﬁcant correlation with fruit width, average fruit weight and number of fruits/plant at both genotypic and phenotypic levels. Path coeﬃcient analysis revealed highly positive direct contribution towards yield/plant with number of fruits/plant, fruit width and average fruit weight at both genotypic and phenotypic level. On the other hand, vine length, days to ﬁrst ﬂowering bud, days to ﬁrst fruit setting, days to ﬁrst fruit picking and fruit length showed negative direct eﬀect on fruit yield/pant.